The effectiveness of tibial nerve stimulation in managing chronic anal fissures: Systematic review and meta-analysis - Elnibras, Mohammed; Brnawi, Haneen; Shawir, Mohammad (Edelweiss Applied Science and Technology, 2025)
Surgical sphincterotomy, such as lateral internal sphincterotomy (LIS), and chemical sphincterotomy, such as Glyceryl Trinitrate (GTN) or Botulinum Toxin (BT), have been the main options for treating chronic anal fissures for many years. However, in recent years, tibial nerve stimulation (TNS) has emerged as a non-invasive alternative for managing this condition. This systematic review and meta-analysis aim to gather evidence on the effectiveness of TNS in treating chronic anal fissures. The authors conducted a comprehensive search across PubMed, Google Scholar, and Web of Science databases, covering publications from January 2000 to January 2024. The search keywords included tibial nerve stimulation, percutaneous tibial nerve stimulation, transcutaneous tibial nerve stimulation, sacral neuromodulation, and anal fissure. A total of 282 studies were identified; after removing duplicates and irrelevant studies based on inclusion and exclusion criteria, six studies were included in the analysis. The healing rates for LIS, TNS, and GTN are 92.2%, 63.1%, and 67.5%, respectively. The healing rate for LIS is statistically significantly higher than that for TNS, while there is no statistically significant difference between the healing rates of TNS and GTN. The complication rates for GTN, LIS, and TNS are 7.5%, 1.3%, and 0%, respectively. The rate of complications is higher in GTN and LIS compared to TNS; however, this difference is not statistically significant. The recurrence rates for TNS, GTN, and LIS are 21.3%, 9.3%, and 2.8%, respectively. The recurrence rate for TNS is statistically significantly higher than that for LIS, while there is no statistically significant difference between the recurrence rates of TNS and GTN. Although LIS remains the gold standard procedure for chronic anal fissures due to its high success rate and low recurrence rate, TNS has emerged as a promising non-invasive treatment option with a favorable success rate and no reported complications.